2018
DOI: 10.2134/jeq2018.06.0242
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Subsurface Phosphorus Discharge from a Clay Soil in a Nine‐Year Study Comparing No‐Till and Plowing

Abstract: No‐till as a water protection measure is highly efficient in controlling erosion and particulate P (PP) loss but tends to increase dissolved reactive P (DRP) concentrations in runoff water. In a 9‐yr field study on a clay soil in Southwest Finland, the effects of no‐till and autumn plowing on surface runoff and subsurface drainage water quality were compared. The site had a 2% slope and was under spring cereal cropping, with approximately replacement fertilizer P rates. Vertical stratification of soil‐test P t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 63 publications
4
20
1
Order By: Relevance
“…Lower SRP concentrations recorded in flow through field drains under natural rainfall in the United Kingdom are also in line with previous studies (Haygarth et al, 1998; Withers et al, 2009b), although this trend was not observed under Finnish conditions. This may be due to the more strongly structured clay soils in Finland, where rapid flow along cracks and biopores decreases the contact time between percolating water and subsoil (Uusitalo et al, 2018). …”
Section: Resultsmentioning
confidence: 99%
“…Lower SRP concentrations recorded in flow through field drains under natural rainfall in the United Kingdom are also in line with previous studies (Haygarth et al, 1998; Withers et al, 2009b), although this trend was not observed under Finnish conditions. This may be due to the more strongly structured clay soils in Finland, where rapid flow along cracks and biopores decreases the contact time between percolating water and subsoil (Uusitalo et al, 2018). …”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis comparing P losses of conservation versus conventional tillage demonstrated a 40% increase in both SRP concentration and load due to conservation tillage, although the amount varied based on rainfall (Daryanto et al, 2017). Other studies have demonstrated SRP increases from land under conservation tillage (Dodd and Sharpley, 2016; Jarvie et al, 2017; Renwick et al, 2018; Uusitalo et al, 2018). The increase in SRP with conservation tillage was relative to the reduction in sediment‐attached P, which may actually increase degradation of water quality since SRP is more bioavailable.…”
Section: Implementing Conservation Practices That Reduce Agriculturalmentioning
confidence: 91%
“…Dodd and Sharpley (2016) noted a range for particulate P reduction due to conservation tillage from −33 to 96% compared with 45 to 89% for grassed waterways. Following 9 yr of research on a clay soil in Finland, Uusitalo et al (2018) demonstrated that particulate P loads and concentrations were 27 and 55% lower, respectively, with no‐till than with conventional till.…”
Section: Implementing Conservation Practices That Reduce Agriculturalmentioning
confidence: 99%
“…The effect of tillage on near-saturated K(h) was examined in Kotkanoja leaching field at Jokioinen (Turtola et al 2007). The soil at the field site is classified as a Protovertic Luvisol (Clayic, Cutanic) and its topsoil clay content ranges from 50 to 60 % (Uusitalo et al 2018). The measurements reported here were performed in summer 2017 and 2018 in a no-till plot (KO B) and a ploughed plot (KO C) (Table S1).…”
Section: Effects Of Tillage Systems On Soil Near-saturated K(h)mentioning
confidence: 99%
“…Plot KO C is autumn-ploughed annually and harrowed in May for seedbed preparation. Full details of the management regime for the Kotkanoja field can be found in Uusitalo et al (2018). Measurements were performed four times (with four replicates) in both 2017 and 2018 except in plot KO C, which was ploughed on the last measurement occasion in 2018.…”
Section: Effects Of Tillage Systems On Soil Near-saturated K(h)mentioning
confidence: 99%